Effect of a dislocation pile-up at the neutral axis on trans-crystalline crack growth for micro-bending fatigue. (January 2017) - Eisenhut, Lena; Schaefer, Florian; Gruenewald, Patrick; Weiter, Laura; Marx, Michael; Motz, Christian
Highlights: Trans-crystalline fatigue crack growth in CMSX-4 micro-beam implemented. Dislocation pile-up causes crack deceleration at the neutral axis of a micro-beam. Bauschinger effect resulting from a dislocation pile-up during micro-beam fatigue. Crack growth curve gathered by combination of FEM-simulations and experiment. Fatigue crack growth in micro-beams needs higher stress intensity factor ranges. Abstract: Micro-bending beams of the f.c.c. nickel based superalloy CMSX-4, machined by the focused ion beam technique (FIB), are used to study the effect of a stress gradient associated with the bending configuration on the fatigue crack growth behavior in small dimensions. To avoid an impact of dislocation reactions on the crack growth behavior, a trans-crystalline stage-I fatigue crack has been initiated at a notch placed on a slip plane in a single-slip geometry with the highest Schmid factor. d a /d N -curve data was gathered by visual crack extension observation during in-situ fatigue in the SEM combined with experimental compliance measurements and FEM-simulations. A dislocation pile-up at the neutral axis results in a significant Bauschinger effect and a back stress acting on the crack tip causing a crack deceleration and an early change from stage-I to stage-II fatigue crack growth analyzed by FIB tomography.